Foreign Experience of Assessing the Quality and Reliability of the Functioning of Urban Public Passenger Transport - Sayidyusupov Marufkhon (Global Scientific Publishing, 2022)
In recent years, the demand for urban public passenger transport services has increased markedly, this is due to the transport policy of cities in many countries, aimed at the priority development of urban public passenger transport systems. The article discusses the analysis of foreign experience in assessing the quality and reliability of the operation of urban public passenger transport.
Keywords: Urban public passenger transport; quality and reliability assessments; population mobility; traffic schedule